PENGARUH PENGGUNAAN PULL BUOY DAN PAPAN LUNCUR TERHADAP PENGUASAAN GERAK GAYA BEBAS LES RENANG TINGKAT SD DI SANGGARIANG KUNINGAN - Beny Dwi Febriawaludin (STKIP Muhammadiyah Kuningan, 2021)
The purpose of this study was to determine whether the use of a pull buoy and a skateboard has an effect on the mastery of freestyle swimming lessons at the elementary school level in Sanggariang Kuningan. The research method used in this research was experimental. The population observed was all students of elementary school swimming lessons in Sanggariang Kuningan as many as 22 people. The sample selection was based on purposive sampling technique so that the sample of this study was 22 students of elementary school swimming lessons in Sanggariang Kuningan divided into 2 groups, namely the experimental group using a pull buoy and the control group using a skateboard, each group of 11 people. The research instrument used a freestyle swimming test which was analyzed through the Mann Whitney test. The results showed that the significance value for Mann-Whitney U was 0.001 < 0.05, so Ho was rejected and Ha was accepted, meaning that there was a difference in mastery of freestyle movement between the experimental group and the control group. Thus, the use of pull buoys and skateboards has an effect on mastery of freestyle swimming lessons at the elementary school level at Sanggariang Kuningan.